Endoscopic botulinum toxin injection for treatment of pharyngeal dysphagia in patients with cricopharyngeal dysfunction. (2nd November 2018) - Jeong, Seok-Hoo; Kim, Yu Jin; Kim, Yoon Jae; Park, Ki Deok; Kim, Eui Joo; Chung, Jun-Won; Kwon, Kwang An; Kim, Kyoung Oh; Park, Dong Kyun; Kim, Jung Ho; Cho, Jae Hee
Abstract: Background: Dysphagia associated with neurologic disorders is a problem worldwide. However, few studies have assessed the efficacy of endoscopic botulinum toxin injections into the cricopharyngeal muscle using a pharyngoscope. Methods: Fourteen patients who received an endoscopic botulinum toxin injection due to cricopharyngeal muscle dysfunction and a neurological disorder from 2006 to 2017 were retrospectively reviewed at a single tertiary medical center. The toxin was injected at a 100 international unit (IU) total dose under direct endoscopic vision. The success of the procedure was evaluated comprehensively using the following: clinical resolution of the previous symptoms, functional oral intake scale (FOIS) for the clinical evaluation of swallowing, and videofluoroscopic swallowing study (VFSS) to check decreased retention of barium at the pyriform sinus and the epiglottic vallecula. Results: The study included 12 males and 2 females (mean age, 58 years old; range, 37–82 years). Three patients (21.4%) were confirmed clinically and eleven were confirmed by VFSS. Eleven patients (78.6%) were managed successfully with the injection. Three patients (21.4%) did not improve despite the injection. Conclusion: An endoscopic botulinum toxin injection may be a good treatment option for patients with dysphagia and cricopharyngeal dysfunction due to a neurological disorder. Large, prospective, long-term follow-up studies are needed in the future.